Mental Health Nursing: waiting room intervention in integral health care - Juliana Macedo Melo Andrade; Marciana Gonçalves Farinha; Elizabeth Esperidião (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To describe and to analyze the proposal for intervention in the waiting room as a possibility for Nursing in mental health in group context. Method: Descriptive study with a qualitative approach, convergent care type, developed in a Psychosocial Care Center for Alcohol and Drugs in the interior of the state of Goiás. Results: The service in the waiting room provided moments of reflection, knowledge, learning, listening and exchanging experiences. Final considerations: The meetings in the waiting room favored the articulation between theoretical knowledge and the practice of nursing care in groups, constituting a space with a valuable locus for the development of educational and support actions in health services, to be undertaken by the nurse and, also, by other professionals of the health team.